2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696380
|View full text |Cite
|
Sign up to set email alerts
|

Normal distributions transform Monte-Carlo localization (NDT-MCL)

Abstract: Abstract-Industrial applications often impose hard requirements on the precision of autonomous vehicle systems. As a consequence industrial Automatically Guided Vehicle (AGV) systems still use high-cost infrastructure based positioning solutions. In this paper we propose a map based localization method that fulfills the requirements on precision and repeatability, typical for industrial application scenarios. The proposed method -Normal Distributions Transform Monte Carlo Localization (NDT-MCL) is based on a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 14 publications
0
55
0
Order By: Relevance
“…In severe cases this results in wrong associations between map and observation, which causes the pose distribution to diverge. On the other hand, in [1] it was shown that the maximum aposteriori estimate of NDT-MCL is very accurate in static environments. The accuracy also decreased minimally in the presence of dynamic objects (e.g.…”
Section: B Dual-timescale Ndt-mclmentioning
confidence: 99%
See 3 more Smart Citations
“…In severe cases this results in wrong associations between map and observation, which causes the pose distribution to diverge. On the other hand, in [1] it was shown that the maximum aposteriori estimate of NDT-MCL is very accurate in static environments. The accuracy also decreased minimally in the presence of dynamic objects (e.g.…”
Section: B Dual-timescale Ndt-mclmentioning
confidence: 99%
“…Normal Distribution Transform Monte-Carlo Localization (NDT-MCL) was introduced in [1]. It employs NDT [2,3] to represent both, the map and the measurements.…”
Section: A Ndt-mclmentioning
confidence: 99%
See 2 more Smart Citations
“…A 3D range sensor (Velodyne HDL-32E) is used for mapping and localization. Mapping is carried out with the NDTFusion algorithm [12], while NDT-MCL [13] is used for the localization. First, an exploration plan for gas detection was generated using the conv-SPP algorithm in [2].…”
Section: Real World Experimentsmentioning
confidence: 99%